Passiflora edulis: new natural host of Melochia yellow mosaic virus in Brazil - Spadotti, D. M.A.; Bello, V. H. [UNESP]; Favara, G. M.; Stangarlin, O. S.; Krause-Sakate, R. [UNESP]; Rezende, J. A.M. (Springer Nature, 2019)
Begomovirus infections in Passiflora plants in Brazil have increased in recent years. This contribution reports natural infection of Passiflora plants by Melochia yellow mosaic virus (MelYMV) in the state of Mato Grosso do Sul. MelYMV was transmitted to Passiflora plants by biolistics but not by Bemisia tabaci MEAM1 and MED. To our knowledge this is the first report of MelYMV infecting Passiflora plants.
Keywords: Begomovirus; Bemisia tabaci; Diagnosis; Passifloraceae